Giving or taking: the role of dispositional power Motivation and positive affect in profit maximization? - Markus Quirin; Martin Beckenkamp; Julius Kuhl (Max Planck Institute for Research on Collective Goods, 2008)
Socio-economic decisions are commonly explained by rational cost vs. benefit considerations, whereas person variables have not usually been considered. The present study aims at investigating the degree to which dispositional power motivation and affective states predict socio-economic decisions. The power motive was assessed both indirectly and directly using a TAT-like picture test and a power motive self-report, respectively. After nine months, 62 students completed an affect rating and performed on a money allocation task (Social Values Questionnaire). We hypothesized and confirmed that dispositional power should be associated with a tendency to maximize one's profit but to care less about another party's profit. Additionally, positive affect showed effects in the same direction. The results are discussed with respect to a motivational approach explaining socio-economic behaviour.
Keywords: C91; D01; Z13; 330; economic decision-making; rational choice theory; personality; implicit power motive; positive affect; operant motive test; Entscheidung; Rationales Verhalten; Persönlichkeitspsychologie; Emotion; Soziale Werte; Ökonomisches Prinzip; Test